2015
DOI: 10.3126/ije.v4i1.12180
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution to the Seasonal Distribution and Biodiversity of Fresh Water Phytoplankton of Karagam Lake, Srikakulam, Andhra Pradesh, India

Abstract: In the present study, Seasonality and Species diversity of Phytoplankton studies were made on the Karagam Lake of Srikakulam District, Andhra Pradesh from November 2006 to October 2008. The phytoplankton population was represented by a Total taxa of 64 genera were recorded in this study. This includes Chlorophyceae (26 genera- 74 species), Bacillariophyceae (18 genera-41species), Cyanophyceae (17 genera-39 species) and Euglenophyceae (3 genera-8species). The abundant algal forms belong to Volvocales (9 genera,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The dominance of different algal classes in this lake was reported as Bacillariophyceae and Zygnematophyceae (29% each), Chlorophyceae (18%), Cyanophyceae (14%), Euglenophyceae (8%) and Ulvophyceae (2%) (Figure 3B). Jyotsna et al (2015) also observed maximum members of Bacillariophyceae in Karagam Lake, Srikakulam, Andhra Pradesh, India. Similarly, Vyas and Kumar (1968) observed higher Euglenophyceae population in post-monsoon season.…”
Section: Seasonal Variation Of Algal Diversity In Lakementioning
confidence: 74%
“…The dominance of different algal classes in this lake was reported as Bacillariophyceae and Zygnematophyceae (29% each), Chlorophyceae (18%), Cyanophyceae (14%), Euglenophyceae (8%) and Ulvophyceae (2%) (Figure 3B). Jyotsna et al (2015) also observed maximum members of Bacillariophyceae in Karagam Lake, Srikakulam, Andhra Pradesh, India. Similarly, Vyas and Kumar (1968) observed higher Euglenophyceae population in post-monsoon season.…”
Section: Seasonal Variation Of Algal Diversity In Lakementioning
confidence: 74%
“…3) and have higher growth of diatoms (Fig.1). Jyotsna et al (2014) also observed maximum members of Bacillariophyceae in the month of April. According to Munawar (1970) regular supply of nitrate encouraged the growth of diatoms.…”
Section: Discussionmentioning
confidence: 99%